Impacts of long‐term elevated atmospheric CO2 concentrations on communities of arbuscular mycorrhizal fungi. Issue 14 (17th July 2019) - Maček, Irena; Clark, Dave R.; Šibanc, Nataša; Moser, Gerald; Vodnik, Dominik; Müller, Christoph; Dumbrell, Alex J.
Abstract: The ecological impacts of long‐term elevated atmospheric CO2 (eCO2 ) levels on soil microbiota remain largely unknown. This is particularly true for the arbuscular mycorrhizal (AM) fungi, which form mutualistic associations with over two‐thirds of terrestrial plant species and are entirely dependent on their plant hosts for carbon. Here, we use high‐resolution amplicon sequencing (Illumina, HiSeq) to quantify the response of AM fungal communities to the longest running (>15 years) free‐air carbon dioxide enrichment (FACE) experiment in the Northern Hemisphere (GiFACE); providing the first evaluation of these responses from old‐growth (>100 years) semi‐natural grasslands subjected to a 20% increase in atmospheric CO2 . eCO2 significantly increased AM fungal richness but had a less‐pronounced impact on the composition of their communities. However, while broader changes in community composition were not observed, more subtle responses of specific AM fungal taxa were with populations both increasing and decreasing in abundance in response to eCO2 . Most population‐level responses to eCO2 were not consistent through time, with a significant interaction between sampling time and eCO2 treatment being observed. This suggests that the temporal dynamics of AM fungal populations may be disturbed by anthropogenic stressors. As AM fungi are functionally differentiated, with different taxa providing different benefits to host plants, changes in population densities in response to eCO2 may significantly impact terrestrial plant communities and their productivity. Thus, predictions regarding future terrestrial ecosystems must consider changes both aboveground and belowground, but avoid relying on broad‐scale community‐level responses of soil microbes observed on single occasions.